Synthesis and spectroscopic characterization of cholesteryl hydrogen phthalate and its derivatives - PF, Ng; TW, Sam; MC, Feng; CB, Yeoh; MG, Tay (India National Science Academy , India., 2004)
The synthesis and spectroscopic characterization of cholesteryl hydrogen phthalate and its derivatives (methyl-, ethyl-, isopropyl- , di- and stigmasteryl-) are reported in this paper. Cholesterol as well as phthalic anhydride have been used as the starting materials in preparing cholesteryl hydrogen phthalate. This compound was followed by the esterification of half ester by refluxing with methanol , ethanol and isopropanol, respectively. In preparation of dicholesteryl phthalate and stigmasteryl cholesteryl phthalate, esterification with direct heat method has been tried. All the compounds are characterized by NMR (1H and 13C) and FTIR spectra.